Firm-Specific Determinants of Bank Liquidity in Indonesia - Akbar, Maulana; Fadilla, Akhmal Aries; Lestari, Henny Setyo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study aims to examine the firm-specific determinants that influence bank liquidity among conventional commercial banks in Indonesia during the period 2019–2023. Using panel data regression on a sample of 23 banks listed on the Indonesia Stock Exchange, the study analyzes the impact of six independent variables—Capital Adequacy Ratio (CAR), Total Loan to Total Assets Ratio (TLTAR), Interest Rate Margin (IRM), Deposit Ratio, Non-Performing Loans (NPL), and Return on Assets (ROA)—on the liquidity ratio (measured as liquid assets to total assets). The results show that CAR has a significant positive effect, while TLTAR has a significant negative effect on bank liquidity. Other variables such as IRM, deposits, NPL, and ROA were found to have no significant influence. These findings indicate that adequate capital reserves and balanced credit allocation are crucial for maintaining liquidity in Indonesian banks. The study contributes to the literature by providing empirical evidence from the Indonesian banking sector and offers insights for bank managers and regulators to develop policies that enhance financial stability.